INTEGRATED CHILD DEVELOPMENT SERVICES (ICDS) SCHEME :A JOURNEY OF 37 YEARS - Gupta, A; Gupta, S K; Nongkynrih, Baridalyne (Indian Journal of Community Health, 2013)
Background: Malnutrition is currently one of the biggest challenges facing the modern world. In India, the Integrated Child Development Services (ICDS) scheme was started with the objective of improving child health, nutrition and development. Since its inception in 1975, the outreach of ICDS services has increased enormously, and now the goal is universalization of ICDS. In recent years ICDS has been evaluated by many agencies which have resulted in numerous changes to achieve the objectives. Methods: This paper reviews the functioning and progress of Integrated Child Development Services and attempts to identify the programme bottlenecks Results: Since its inception, ICDS has expanded rapidly in its scope and coverage, and today it covers approximately 7.6 million pregnant women and lactating mothers and around 36 million children less than six years of age. Although there had been vast increase in ICDS blocks, it was seen that there is lack of infrastructure and basic amenities. Though immunization activities under ICDS have appreciable credibility, however, non-formal pre-school, nutrition and health education are not fully functioning in the way they were planned to be. Conclusion: The ICDS has a huge potential as a platform to provide comprehensive maternal and child services. Although there is a wide coverage under the ICDS blocks, many of them are not functioning optimally. Infrastructure and basic amenities, and training components need to be strengthened.